"Variables of Sports Competition as Correlate of Physiological and Social Development of Tertiary School Athletes" - Garcia, Bernice Jacob (International Journal of Arts, Sciences and Education, 2023)
This study aims to ascertain the Variables of Sports Competition as Correlates to the Physiological and social Development of Tertiary School Athletes. It is a quantitative research that utilizes a descriptive - corellational method of research. Furthermore, it utilizes sets of questionnaires with 103 student athletes from Marinduque State College who are enrolled in Academic Year 2021- 2022 and Academic year 2022- 2023. The findings of the study revealed that majority of the athletes are preparing for a regional sport competition in 1 month duration before the competition or also known as their rigid training. Most of the participants disclosed that they have a coach who has an empathetic style that values sportsmanship above all and make decision that consider the athletes’ opinion. Furthermore, the participants disclosed that majority of them receives cash incentives if the athlete won a medal (bronze, silver, or gold) in a competition and gain a monthly allowance being a varsity athlete in regards to awards and incentive they receive. Moreover, participants revealed that the institution they belong creates an interventive programs for student – athlete development. Respondents of the study perceived that peer support is the most essential in sports competition related variable. Majority of them exposed that their peers support them and cheer them up when they feel down in their performance in a competition and shows their intention as proud team mates and peers. Lastly, the salient findings of the study revealed that the correlation of sports related variables and physiological development of athletes are significantly related to each other. Likewise, as to social development of athletes, the result of the study disclosed that the correlation of Sports related variables and social development of athletes are significantly related to each other as well. Keywords: Sports Competition Related Variables, Physiological Development of Athletes, Social Development of Athletes.